Successful Removal of a Chronic Aspirated Foreign Body after Twelve Years - Reddy, Radhika Z. (Case Rep Pulmonol, 2018)
Chronic retention of aspirated foreign bodies is rare but can result in indolent systemic and respiratory symptoms. Bronchoscopy may show features of tissue reaction to the foreign body, including granulation tissue, endobronchial stenosis, strictures, edema, and airway distortion. The diagnosis of foreign body aspiration is often difficult to establish since some patients may not give a clear history of aspiration or may present late. In addition, patients may be misdiagnosed with chronic pneumonia, bronchitis, asthma, or malignancy. We present the case of a 42-year-old male who had a chronically retained piece of an aluminum beverage container in the left mainstem bronchus for 12 years. Careful history, radiographic evaluation, and bronchoscopic examination revealed the foreign body, which was successfully extracted by rigid bronchoscopy.